Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi di Jawa Barat Periode 1989-2008 - Alamsyah, Mochamad Reza; Setiarso, Oke; Sutopo, Indi (Lingka Ekonomika, 2024)
This research entitled "Analysis of Factors Affecting Economic Growth In West Java the Period 1989-2008". The purpose of this research is to identify the influence of Domestic Investment, Foreign Investment, and labor to economic growth in West Java Province period 1989-2008, and to know which are the most influential variable on economic growth in the province of West Java, period 1989-2008 . Based on data analysis, variable Domestic Investment, Foreign Investment, and labor have positive and significant jointly or partially to economic growth in West Java province in the period 1989-2008. The variables that most influence on economic growth in West Java Province period 1989-2008 is labor. The implications of this research is the West Java Provincial Government should be able to maintain and further enhance its economic growth, through the implementation of a planned and sustainable development. By creating a force capable of promoting economic growth in West Java province, the local government needs to improve the quality and quantity of investment. Therefore it is desirable for all parties involved participate in and support for more mengerakkan investment activities in West Java Province. Efforts that can be done, such as by providing basic infrastructure facilities and both public and social infrastructure, improvement of the bureaucracy and business licensing by licensing procedure that is easy, fast, transparent, and have legal certainty. To increase labor productivity will require serious attention, through improving the quality of manpower by organizing training centers, informal courses, programs increase work motivation and improving the welfare of workers as a guarantee of safety, social security, and assurance of adequate wages according to minimum standards applicable.